Differential preferences for RBCs is key for Plasmodium species evolutionary diversity within human host - Djidjou‐Demasse, Ramsès; Mann‐Manyombe, Martin L.; Seydi, Ousmane; Yatat‐Djeumen, Valaire (Studies in applied mathematics (Cambridge), 2022)
Plasmodium species exhibit differential preferences for red blood cells (RBCs) of different ages. From a fundamental standpoint, we propose an age‐structured within‐host malaria model taking into account the variation in RBCs preference. We show that such a differential ecological characteristic of Plasmodium species within their human host is fundamental to capture species diversity within the same infected host individual. We show that with such difference in the RBCs preferences, the long‐term coexistence of different species is possible under a certain condition, basically based on a suitable order on the basic reproduction numbers of each species. In particular, we show that the dynamical behavior of the model is not trivial and can range from the extinction of all species, the persistence of a single species, to the coexistence of more than one species. We also describe how our general analysis can be applied in some coinfection configurations including three malaria species: Plasmodium falciparum, Plasmodium vivax, and/or Plasmodium malariae. This improved understanding of the within‐host parasite multiplication in a context of mixed Plasmodium species interactions.